Replication Data for: Projected shifts in Coffea arabica suitability among major global producing regions due to climate change - Ovalle Rivera, Oriana; Läderach, Peter R.D.; Bunn, Christian; Obersteiner, Michael; Schroth, Götz (2015)
The dataset has 2194 coffee location points. Most of the data came from projects developed by the International Center for Tropical Agriculture (CIAT) in collaboration with other research centers and producer cooperatives. We modeled the global distribution of Arabica coffee under changes in climatic suitability by 2050s as projected by 21 global circulation models.